2016
DOI: 10.1097/dbp.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Executive Function and Problematic Adolescent Driving

Abstract: Objective Motor vehicle collisions (MVCs) are one of the leading causes of injury and death for adolescents. Driving is a complex activity that is highly reliant on executive function to safely navigate through the environment. Little research has examined the efficacy of using self-reported executive function measures for assessing adolescent driving risk. This study examined the Behavior Rating Inventory of Executive Function (BRIEF) questionnaire and performance based-executive function tasks as potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 60 publications
(108 reference statements)
4
32
0
Order By: Relevance
“…The results from previous studies in the field of road safety measuring executive functions with different instruments demonstrate that executive functions can be considered as an indicator of problematic driving behavior. This fact is cross validated with other approaches for assessment of risky driving behavior [22,23]. Similarly to these findings, the results from the presented studies show that the proposed instrument is a valid tool for prevention of dangerous driving and can be used as part of different batteries for measurement of driving performance.…”
Section: Discussionsupporting
confidence: 75%
“…The results from previous studies in the field of road safety measuring executive functions with different instruments demonstrate that executive functions can be considered as an indicator of problematic driving behavior. This fact is cross validated with other approaches for assessment of risky driving behavior [22,23]. Similarly to these findings, the results from the presented studies show that the proposed instrument is a valid tool for prevention of dangerous driving and can be used as part of different batteries for measurement of driving performance.…”
Section: Discussionsupporting
confidence: 75%
“…Although, the BRIEF-A shows little statistical association with performance-based measures (Ritter, Perrig, Steinlin, & Everts, 2014) further investigation into the relationship between the two types of executive function is needed in the context of driving. It could be the case that the BRIEF-A captured variance not explained by traditional performance-based measures and may be tapping into “hot cognition” that is not always captured with “cool cognition” in-lab performance-based measures (see Hongwanishkul, Happaney, Lee, & Zelazo, 2005; Prencipe et al, 2011) as the BRIEF has shown association with negative driving outcomes (Pope et al, in press; Rike et al, 2015; Rike et al, 2014). We also did not measure impulsivity, a trait associated with distracted driving and executive deficit or self-regulation, a compensation strategy involving awareness of cognitive and motor deficits frequently seen in older drivers that factor into a driver’s willingness to engage in certain driving behaviors (Lerner, Singer, & Huey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A) (Roth, Isquith, & Gioia, 2005) assesses behavioral disruptions spanning nine domains of executive function (inhibit, shift, emotional control, self-monitor, initiate, working memory, plan/organize, task monitor, and organization of materials) over the past month. Previous research has shown the BRIEF to be related to negative driving outcomes in individuals after brain injury (Rike, Johansen, Ulleberg, Lundqvist, & Schanke, 2015; Rike, Ulleberg, Schultheis, Lundqvist, & Schanke, 2014) and with adolescent drivers (Pope, Ross, & Stavrinos, in press). To our knowledge no other study has assessed the BRIEF in relation to engagement in distracted driving.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific role of EF constructs in driving performance has not been examined systematically in adolescent drivers [ 31 ]. In order to improve teen driver safety and reduce injury and death on the roads, it is crucial that we better understand which discrete domains and sub-processes of EF are key to safe driving so that training and other countermeasures can be geared towards addressing the root causes of adolescent crashes.…”
Section: Introductionmentioning
confidence: 99%